Risk-Based Internal Oversight of Local Government Finance: A Literature Review on Fraud Prevention and Control - Geofanny Edo Pratama; Dian Ferriswara; Sarwani Sarwani; Sri Kamariyah (International Forum of Researchers and Lecturers, 2026)
Local governments manage substantial public resources under conditions of decentralization, fiscal complexity, and heightened accountability demands, making them particularly vulnerable to financial mismanagement and fraud. In this context, risk-based internal oversight has increasingly been promoted as a governance-oriented alternative to traditional compliance-based supervision. This literature review article examines how risk-based internal oversight is conceptualized, operationalized, and linked to fraud prevention and control in the management of local government finance. The study addresses a central problem in the existing literature: the fragmentation of analytical perspectives across risk-based internal auditing, fraud risk management, internal control systems, public financial management, and public accountability, which has limited a comprehensive understanding of how internal oversight contributes to safeguarding public funds. The primary objective of this article is to synthesize and integrate these strands of literature to clarify the role of risk-based internal oversight as a systemic governance mechanism for fraud prevention and control at the subnational level. Methodologically, the study employs an integrative literature review approach, drawing on peer-reviewed journal articles and authoritative institutional publications indexed in major academic databases over the past decade. A structured search, screening, and thematic synthesis process was applied to identify patterns, convergences, and divergences across conceptual, empirical, and policy-oriented studies. The findings indicate a clear shift from compliance-oriented inspection toward risk-based internal oversight that prioritizes high-risk financial processes—particularly procurement, grants, and asset management—where fraud risks are most pronounced. The synthesis further shows that effective fraud prevention depends on the alignment of risk-based oversight with fraud risk management practices, robust internal control systems (including SPIP).